Recombinant plants provide a new approach to the production of bacterial polysaccharide for vaccines - Smith, Claire M.; Fry, Stephen C.; Gough, Kevin C.; Patel, Alexandra J.F.; Glenn, Sarah; Goldrick, Marie; Roberts, Ian S.; Whitelam, Garry C.; Andrew, Peter W. (Public Library of Science, 2014)
Bacterial polysaccharides have numerous clinical or industrial uses. Recombinant plants could offer the possibility of producing bacterial polysaccharides on a large scale and free of contaminating bacterial toxins and antigens. We investigated the feasibility of this proposal by cloning and expressing the gene for the type 3 synthase (cps3S) of Streptococcus pneumoniae in Nicotinia tabacum, using the pCambia2301 vector and Agrobacterium tumefaciens-mediated gene transfer. In planta the recombinant synthase polymerised plant-derived UDP-glucose and UDP-glucuronic acid to form type 3 polysaccharide. Expression of the cps3S gene was detected by RT-PCR and production of the pneumococcal polysaccharide was detected in tobacco leaf extracts by double immunodiffusion, Western blotting and high-voltage paper electrophoresis. Because it is used a component of anti-pneumococcal vaccines, the immunogenicity of the plant-derived type 3 polysaccharide was tested. Mice immunised with extracts from recombinant plants were protected from challenge with a lethal dose of pneumococci in a model of pneumonia and the immunised mice had significantly elevated levels of serum anti-pneumococcal polysaccharide antibodies. This study provides the proof of the principle that bacterial polysaccharide can be successfully synthesised in plants and that these recombinant polysaccharides could be used as vaccines to protect against life-threatening infections.